Community acquired Stenotrophomonas maltophilia causing empyema in an adult with HIV - Sharma, P.; Duggal, S.D.; Gupta, S.; Gur, R.; Kaushik, S.; Bharara, T. (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: Stenotrophomonas maltophilia (S. maltophilia) is multidrug resistant (MDR) organism usually associated with hospital acquired infections. Here we report a rare case of community acquired S. maltophilia empyema in a human immunodeficiency virus (HIV) positive patient. Case Report: A 54 year old male presented with cough, breathlessness and chest pain for one month. On investigation, radiological picture was suggestive of massive right empyema. Pleural fluid culture grew S. maltophilia repeatedly which was treated with cotrimoxazole and levofloxacin based on antibiogram. Following improvement patient was discharged on anti-retro viral and anti-tubercular treatment. Conclusion: Community acquired invasive S. maltophilia infections should be kept as differential diagnosis in immunocompromised patients. Being MDR, appropriate microbiological identification and susceptibility play an important role in treatment and outcome of these patients.